2019
DOI: 10.1038/s41598-019-47486-w
|View full text |Cite
|
Sign up to set email alerts
|

Improved efficacy of naproxen-loaded NLC for temporomandibular joint administration

Abstract: Inflammatory conditions of the temporomandibular joint (TMJ) and peripheral tissues affect many people around the world and are commonly treated with non-steroidal anti-inflammatory drugs (NSAIDs). However, in order to get desirable results, treatments with NSAIDs may take weeks, causing undesirable side effects and requiring repeated administration. In this sense, this work describes the development of an optimized nanostructured lipid carrier (NLC) formulation for intra-articular administration of naproxen (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 41 publications
2
25
0
Order By: Relevance
“…Lipoid nanoDDS loaded with naproxen (NPX) with EE 99.8% designed for intra-articular administration was tested in a rat model of acute inflammation of the temporomandibular joint. In vivo results showed that the sustained delivery of NPX directly to the affected joint decreased leukocyte and pro-inflammatory IL-1β and TNF-α migration for more than a week, making this nanoformulation a promising candidate for the safe treatment of arthritic states [ 128 ].…”
Section: Designed Nanoddssmentioning
confidence: 99%
“…Lipoid nanoDDS loaded with naproxen (NPX) with EE 99.8% designed for intra-articular administration was tested in a rat model of acute inflammation of the temporomandibular joint. In vivo results showed that the sustained delivery of NPX directly to the affected joint decreased leukocyte and pro-inflammatory IL-1β and TNF-α migration for more than a week, making this nanoformulation a promising candidate for the safe treatment of arthritic states [ 128 ].…”
Section: Designed Nanoddssmentioning
confidence: 99%
“…In addition, Guilherme and colleagues established a nanostructured lipid carrier with the mixture of cetyl palmitate and capric/caprylic triglycerides and the cooperation of Pluronic F68. The deliverer contributed to the administration of naproxen, reducing the IL-1β and TNF-α levels in rat TMJ for over 7 days (Guilherme et al, 2019). Furthermore, mesoporous silica nanoparticles with a core-cone structure were engineered by Li et al, (2019).…”
Section: Novel Delivery Systems For Therapeutic Agentsmentioning
confidence: 99%
“…The acceptor solution containing 5 mmol L -1 phosphate-buffered saline at pH 7.4 was kept at 37°C under stirring at 300 rpm (n = 4). 36 The formulations tested (50 μL added in the donor chamber) were 1% BVC S75 , free or encapsulated in the optimized formulations: NLC-L-B or NLC-M-B. At predefined intervals (from 0 to 28 h) samples were collected (200 μL) from the receptor compartment and replaced with a fresh buffer solution to maintain the sink condition, and BVC S75 was quantified by HPLC.…”
Section: Drug Loading (Dl)mentioning
confidence: 99%
“…These results show that the functional excipients chosen were efficient in forming characteristic (rounded) nanoparticles. 16,36,53 One important issue in the characterization of lipid-based nanocarrier systems is the crystallinity of the lipid matrix. The literature describes an association between the crystallinity of the lipid core structure and drug expulsion.…”
Section: Transmission Electron Microscopy (Tem) Dsc and Xrd Measurementsmentioning
confidence: 99%